2022
DOI: 10.7759/cureus.32847
|View full text |Cite
|
Sign up to set email alerts
|

Infective Endocarditis as a Complication of Crohn’s Disease on Immunotherapy

Abstract: A patient with a history of Crohn's disease on infliximab presented to the hospital with sepsis and a new heart murmur. He was found to have native aortic valve infective endocarditis from a rare species of group D Streptococcus in his blood. The patient was also noted to be in an acute flare of Crohn's disease. The hospital course was complicated by florid heart failure from acute aortic insufficiency. He eventually improved after source control and appropriate antibiotic therapy. S. pasteuranis bacteremia an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Data from two large urban outbreaks in Indianapolis suggested that immunosuppression, older age, and coexisting chronic illnesses were the primary risk factors for acquiring disseminated histoplasmosis [ 18 ]. It is well-known that an immunocompromised state and old age predispose to disseminated infections [ 19 , 20 ]. Of the 66 cases of disseminated histoplasmosis reviewed in the above study, two-thirds of patients reported some combination of central nervous system findings, splenomegaly, hepatomegaly, and lymphopenia [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Data from two large urban outbreaks in Indianapolis suggested that immunosuppression, older age, and coexisting chronic illnesses were the primary risk factors for acquiring disseminated histoplasmosis [ 18 ]. It is well-known that an immunocompromised state and old age predispose to disseminated infections [ 19 , 20 ]. Of the 66 cases of disseminated histoplasmosis reviewed in the above study, two-thirds of patients reported some combination of central nervous system findings, splenomegaly, hepatomegaly, and lymphopenia [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…An optimal diet should be balanced, consisting of lean meat, nuts, fresh fruits and vegetables, and olive oil (Figure 1) [8,9]. A wholesome diet is essential in maintaining a healthy gut flora, which in turn is pivotal in avoiding inflammatory disorders [10][11][12][13]. The primary aim of this review will be to draw attention to the current literature associated with veganism, including the side effects of practicing a VD and long-term consequences for a variety of populations, including adults, adolescents, pregnant and lactating women, and the fetal outcomes of vegan mothers.…”
Section: Introductionmentioning
confidence: 99%